A Comparison of the Stability Performance of Blends of Paraffinic Diesel and Petroleum-Derived Diesel, with RME Biodiesel Using Laboratory Stability Measurement Techniques. (25th February 2015) - de Goede, S.; Wilken, C.; Ajam, M.; Roets, P.; Engelbrecht, P.; Woolard, C.
Abstract : In 2012, a new specification for synthetic fuels containing up to 7% biodiesel (FAME) was approved (CEN TS 15940). This specification allows the sale of neat paraffinic diesel, such as Gas-to-Liquids (GTL) diesel, to captive fleets in Europe. Several aspects are important in the final end-use application, including the stability of the fuel. The current study evaluated the stability of neat GTL diesel and FAME/paraffinic fuel blends via standard laboratory stability tests commonly used to study petroleum-derived fuels. The stability of GTL diesel, containing biodiesel, was evaluated using the Rancimat, PetroOxy, and ASTMD2274 tests. Selected samples were also evaluated using ASTM D5304. The Rancimat results indicated that FAME/GTL diesel blends performed similar to the FAME/petroleum derived fuel blends. In the PetroOxy test, the addition of more than 2 v/v% of a highly stable FAME resulted in an unexpected boost in the stability of the FAME/GTL diesel blend. The ASTM D2274 results were generally insensitive to the addition of FAME. The correlation between the PetroOxy and Rancimant tests was evaluated and found to be base fuel dependent. From this study it was concluded that GTL diesel (in blends with FAME) performed similar to petroleum-derived reference fuels in standard laboratory stability.